PEMULIHAN EKONOMI PASCA COVID-19 MELALUI PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PRODUK OPAK - Ahmad Asrof Fitri; Munawir Sajali; Laela Nurul Fitria; Irfan Amirul Jaiz; Zian Ikhsaniyah Ardi (DEVOSI, 2023)
Covid-19 had given negative effect to all of sectors of human life, particularly in health and economy. In economy sector, the most people affected by covid was workers and those who had micro, small and medium enterprises (MSMEs). In rural area, impact of covid-19 had grown broader by declining people's purchasing power. Inhabitant of Mekarsari village, located in Gantar district in Indramayu City, West Java, for instance, suffered financial loss. Traditional method of marketing and selling was unable to adapt to new behavior of market. The program is based on previous community service program, which was only focused on production. For the reason previously mentioned, this article discusses marketing and production learning program for Opak products is carried out through online media. The methods used in this program are 1) organizing a workshop on digital marketing, 2) making product labels and branding, 3) taking a part in marketing process of Opak. The result showed that the program had significant role in rebranding the product.